Sensor Technologies in Robotics: A Review of Vision, Tactile, and Proximity Sensing Systems - Prashant Roy (International Journal of Robotics and Automation in Mechanics, 2025)
Robotics has undergone remarkable advancements in recent decades, largely driven by the integration of cutting-edge sensor technologies. Sensors serve as crucial for allowing robots to precisely logic, interpret, and react to the world around them. Among the most essential sensor types used in robotics are vision sensors, tactile sensors, and proximity sensors. These technologies strengthen a robot’s capacity for successful navigation, for example, object manipulation, and contact with people and other systems. Vision sensors, including cameras and light detection and ranging (LiDAR) systems, provide robots with the ability to recognize objects, detect motion, and interpret their surroundings through image processing and artificial intelligence techniques. Tactile sensors, on the other hand, mimic the human sense of touch, allowing robotic systems to detect force, texture, and pressure, which is particularly valuable in delicate handling tasks such as medical robotics and industrial automation. Proximity sensors, including ultrasonic and infrared sensors, enable collision avoidance, safe human-robot interaction, and efficient environmental mapping. Notwithstanding those advances, a number of obstacles still stand in the way of the creation and use of detection technologies in robots. Issues such as sensor accuracy, data processing speed, environmental adaptability, and integration with artificial intelligence continue to be active areas of research. Furthermore, ensuring the affordability and scalability of advanced sensors remains a key concern, especially for large-scale industrial and consumer applications. This review examines the latest innovations in vision, tactile, and proximity sensors and their impact on robotic performance. Additionally, it discusses emerging trends, such as sensor fusion, neuromorphic sensing, and artificial intelligence-driven perception systems, which have the potential to revolutionize the next generation of robotics. By addressing current challenges and exploring future research directions, this article highlights the essential role of sensor technology in advancing robotic capabilities across various domains.
Keywords: autonomous navigation; bio-inspired robotics; multi-modal sensing; robotic perception; sensor fusion; tactile feedback